Impact of the Fascia Iliaca Block on Pain, Opioid Consumption, and Ambulation for Patients With Hip Fractures: A Prospective, Randomized Study. Issue 10 (October 2020) - Schulte, Spencer S.; Fernandez, Isaac; Van Tienderen, Richard; Reich, Michael S.; Adler, Adam; Nguyen, Mai P.
Abstract : Objectives: To determine the effect of the fascia iliaca block (FIB) on patients undergoing surgery for hip fractures. Design: Prospective, randomized controlled trial. Setting: Level I trauma center. Patients/Participants: Patients (N = 97) undergoing surgery for hip fractures were prospectively randomized to receive either a perioperative FIB (FIB group) or no block (control group) from February 2018 to April 2019. Main Outcome Measures: Visual analog scale (VAS) score, morphine milligram equivalents, and postoperative ambulatory distance. Results: Fifty-seven patients were randomized to the FIB group, and 40 patients were randomized to the control group. Eighteen patients crossed over from the FIB to the control group, and 12 patients crossed over from the control to the FIB group. In the intent-to-treat analysis, demographic data, mechanism of injury, radiographic fracture classification, and surgical procedure were similar between the 2 groups. The FIB group consumed fewer morphine milligram equivalents before surgery (13 vs. 17, P = 0.04), had a trend toward an improved visual analog scale score on postoperative day 2 (0 vs. 2 P = 0.06), and walked a farther distance on postoperative day 2 (25′ vs. 2′, P = 0.09). A greater proportion of the FIB group were discharged home (50.9% vs. 32.5%, P = 0.05). There were no differences in opioid-related, block-related, or medical complications between groups. In the as-treated and per-protocol analyses, there were no significant differences. Conclusions: A single perioperative FIB for patients with hip fractures undergoing surgery may decrease opioid consumption and increase the likelihood that a patient is discharged home. Level of Evidence: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence.